Reactivity of the EEG characteristics in teenagers with varying degrees of HRV biofeedback training success - D. B. Dyomin (Бюллетень сибирской медицины, 2012)
We consider the nature of the brain bioelectric activity changes in the dynamics of heart rate variability parameters biofeedback sessions in teenagers. There was revealed increase in predominance of the brain functional activity and increase in the stability of the subcortical brain structures. The biggest bioelectric reorganizations are revealed in the right brain hemisphere, often involving the frontal brain lobes. These changes were more pronounced in adolescents with successful completion of training.